A typical neurofibromatosis type 1 in adult with intracranial T2 hyperintensities and pinealoma: A Case Report - Siwei Chen; Haiqiang Jin; Jing Bai; Wei Zhang; Jingjing Luo; Yining Huang; Yongan Sun (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2020)
Neurofibromatosis type 1 (NF-1) is a common autosomal dominant inherited disorder. Aside from typical symptoms like pigmentary manifestation, patients with NF-1 can also have unspecified T2 hyperintensities (T2Hs) on the brain and may develop benign or malignant tumours in central nervous system or other parts of the body. In this article, we reported a 54-year-old female diagnosed as NF-1 combined with T2Hs and pinealoma that was proved to be a high-grade glioma in later follow-up. We noticed some clinical manifestations such as pigmented teeth and dentition defects that had not been described before. There were some reflections from the poor prognosis of this patient. Even though the course of the disease is relatively indolent most of the time, long-term surveillance is in need and treatment may be required in those with symptoms or unstable imaging findings.